Colombian political refugees in Spain: contributions to the field of Social Work from gender and intercultural perspectives - Mut Montalva, Elena (Cuadernos de Trabajo Social, 2018)
The purpose of this article is to provide knowledge in the field of social work, specifically in terms of its practice with women and group intervention with a gender and intercultural focus. Based on the idea that all knowledge is situated, this feminist research underlines the importance of thinking from the perspective of the lives of excluded groups, in this case of Colombian refugees exiled in Spain, in order to make visible their contributions to the defence of human rights, to sustainable human development, and to overcoming vulnerability, through processes of empowerment and creation of support networks. There is reflection on the complexity of political refuge and on its associative practices. Though the drama of exile is an element that affects their life pathways and places them in a subordinate position, the article analyses refugees’ strategies for resistance, resilience and empowerment through activism via associations and platforms. It thereby examines the meaning of diversity as a characteristic that is inherent to contemporary society, in which we coexist with people of diverse cultures, values, religious beliefs, ethnic and gender identities, sexual orientations, social practices, political ideologies and lifestyles, and in particular the meaning of contributions from Colombian refugees settled in Spain.
Keywords: social work; political refugees; intercultural competition; gender; human rights.